Karakterisasi Reservoar menggunakan Inversi AI (Accoustic Impedance) pada Lapangan Stratton, Texas Selatan - Isti Nur Kumalasari; Ordas Dewanto; Bagus Sapto Mulyatno (Jurnal Teknik dan Teknologi Indonesia, 2024)
Currently, oil and natural gas are still the main energy needed by society. To maintain energy security, it is necessary to carry out studies on the characterization of oil and gas field reservoirs. Reservoir characterization is a crucial process in oil and gas field analysis. In this research, reservoir characterization was carried out using AI (Acoustic Impedance) inversion. AI inversion was carried out to determine the distribution of physical parameters in the research area. From the results it can be seen that the AI ​​values ​​based on log data and seismic data are similar. The inversion results show that the gas-filled reservoir zone of the E41 formation has a low AI value. The gas-filled reservoir based on log data is at a depth of 1570-1580 ms and has a value range of 25843-28839 (ft/s*g/cc). The results of the AI ​​inversion volume section show that the gas distribution in the Stratton Field is indicated by low AI values ​​in the West-East distribution direction.